Accuracy and precision of electrical permittivity mapping at 3T: the impact of three B1+ mapping techniques. Issue 6 (8th February 2019) - Gavazzi, Soraya; van den Berg, Cornelis A.T.; Sbrizzi, Alessandro; Kok, H. Petra; Stalpers, Lukas J. A.; Lagendijk, Jan J.W.; Crezee, Hans; van Lier, Astrid L. H. M. W.
Abstract : Purpose: To investigate the sequence‐specific impact of B 1 + amplitude mapping on the accuracy and precision of permittivity reconstruction at 3T in the pelvic region. Methods: B 1 + maps obtained with actual flip angle imaging (AFI), Bloch–Siegert (BS), and dual refocusing echo acquisition mode (DREAM) sequences, set to a clinically feasible scan time of 5 minutes, were compared in terms of accuracy and precision with electromagnetic and Bloch simulations and MR measurements. Permittivity maps were reconstructed based on these B 1 + maps with Helmholtz‐based electrical properties tomography. Accuracy and precision in permittivity were assessed. A 2‐compartment phantom with properties and size similar to the human pelvis was used for both simulations and measurements. Measurements were also performed on a female volunteer's pelvis. Results: Accuracy was evaluated with noiseless simulations on the phantom. The maximum B 1 + bias relative to the true B 1 + distribution was 1% for AFI and BS and 6% to 15% for DREAM. This caused an average permittivity bias relative to the true permittivity of 7% to 20% for AFI and BS and 12% to 35% for DREAM. Precision was assessed in MR experiments. The lowest standard deviation in permittivity, found in the phantom for BS, measured 22.4 relative units and corresponded to a standard deviation in B 1 + of 0.2% of the B 1 + average value. As regards B 1 + precision, in vivo and phantom measurements were comparable. Conclusions: Our simulation framework quantitatively predicts the different impact of B 1 + mapping techniques on permittivity reconstruction and shows high sensitivity of permittivity reconstructions to sequence‐specific bias and noise perturbation in the B 1 + map. These findings are supported by the experimental results.